The Effectiveness of Collaborative Augmented Reality in Gross Anatomy Teaching: A Quantitative and Qualitative Pilot Study. Issue 5 (27th October 2020) - Bork, Felix; Lehner, Alexander; Eck, Ulrich; Navab, Nassir; Waschke, Jens; Kugelmann, Daniela
Abstract : In the context of gross anatomy education, novel augmented reality (AR) systems have the potential to serve as complementary pedagogical tools and facilitate interactive, student‐centered learning. However, there is a lack of AR systems that enable multiple students to engage in collaborative, team‐based learning environments. This article presents the results of a pilot study in which first‐year medical students (n = 16) had the opportunity to work with such a collaborative AR system during a full‐day gross anatomy seminar. Student performance in an anatomy knowledge test, conducted after an extensive group learning session, increased significantly compared to a pre‐test in both the experimental group working with the collaborative AR system ( P < 0.01) and in the control group working with traditional anatomy atlases and three‐dimensional (3D) models ( P < 0.01). However, no significant differences were found between the test results of both groups. While the experienced mental effort during the collaborative learning session was considered rather high (5.13 ± 2.45 on a seven‐point Likert scale), both qualitative and quantitative feedback during a survey as well as the results of a System Usability Scale (SUS) questionnaire (80.00 ± 13.90) outlined the potential of the collaborative AR system for increasing students' 3D understanding of topographic anatomy and its advantages over comparable AR systems for single‐user experiences. Overall, these outcomes show that collaborative AR systems such as the one evaluated within this work stimulate interactive, student‐centered learning in teams and have the potential to become an integral part of a modern, multi‐modal anatomy curriculum.